Uso de antibacterianos en el servicio de cirugía “B” del Hospital Regional Docente de Tujillo, enero – marzo 2007 - Gutiérrez Mendoza, Danny Daniel (2007)
This research work on the "Use of antibacterials in the Department of Surgery "B" Regional Teaching Hospital Trujillo" was held with the objective of describing what are the characteristics of the use of antibacterials and thereby contribute to the rational use the same for which conducted a descriptive study, cross-sectional and prospective, taking population as a unit all medical records of patients hospitalized in sub-servicios neurosurgery, orthopedic surgery, otolaryngology, oncology and urology during the period January to March 2007. For determining the consumption of antimicrobial use is the method of Defined Daily Dose (DDD), the ATC classification, also making use of the methodology established by the MINSA for studies using drugs, reaching the following results: the cefazolin was the antibacterial that had the highest consumption (28.3 DDD / 100 cama-día) and generated by the increased spending (32.2%), in addition to 98% of patients were treated with at least one antibacterial and only 85 .5% of antibacterials used are considered at the request of the National Essential Drugs, finally was sub-servicio neurosurgery who had the highest (2.5) average antibacterials administered per patient. Therefore it is concluded that there are signs of inappropriate use of antibacterial in the Department of Surgery "B" HRDT which warrants more specific investigations